Mandibular bone mineral density in patients with Behçet’s disease - Asutay F; Atalay Y; Acar AH; Asutay H; Eroğlu S; Burdurlu MÇ (Dove Medical Press, 2015)
Fatih Asutay,1 Yusuf Atalay,1 Ahmet Hüseyin Acar,2 Hilal Asutay,3 Selma Eroğlu,4 Muammer Çağrı Burdurlu5 1Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Afyon Kocatepe University, Afyonkarahisar, 2Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Bezmialem Vakif University, Istanbul, 3Department of Prosthodontics, Faculty of Dentistry, 4Department of Physical Therapy and Rehabilitation, Faculty of Medicine, Afyon Kocatepe University, Afyonkarahisar, 5Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Yeditepe University, Istanbul, Turkey Objectives: Behçet’s disease (BD) is a chronic, recurring vasculitis of unknown etiology. Patients with BD may use a lot of medications associated with the clinical symptoms. Drugs that are used in the treatment of BD may cause bone loss. The aims of the current study were to compare the bone mineral density (BMD) values between BD and healthy volunteers and describe the effect of disease duration on mandibular BMD. Materials and methods: The study comprised 30 healthy volunteers (15 males and 15 females, mean age 35.50±6.80 years) and 45 patients with BD (24 males and 21 females, mean age 38.93±8.93 years). The BD group was subdivided according to disease duration (0–5, 6–10, and >10 years). The BMD value of the mandibular body was determined by the dual energy X-ray absorptiometry technique. Results: The mean mandibular body BMD values were 1.294±0.21 g/cm2 in the control group and 1.216±0.22 g/cm2 in the BD patients, although there was no statistically significant difference. The BMD was observed to decrease with increased disease duration but not to a statistically significant degree. Conclusion: The results of this study showed that although the BMD value decreased as the duration of the disease increased, no statistically significant difference was found between the BD patients and the healthy control group. Keywords: Behçet’s disease, mandible, bone mineral density, dual energy X-ray absorptiometry